2016
DOI: 10.5817/cp2016-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Online erotica usage as a mediator between internet addiction and engagement in risky online sexual behaviors

Abstract: In this study, we examined the links between Internet addiction, engagement in online erotica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…The smaller-scale studies identified as part of this review typically reported the percentage of participants who had seen pornography at some point in their lives. Fourteen studies were identified in which more than 90% of the men sampled reported having viewed pornography at some point (Blais-Lecours, Vaillancourt-More, Sabourin, & Godbout, 2016;Bulot, Leurent, & Collier, 2015;D'Abreu, 2013;Donevan & Mattebo, 2017;Drouin & Miller, 2016;Gonsalves, Hodges, & Scalora, 2015;Hald & Mulya, 2013;Kvalem, Traeen, Lewin, & Štulhofer, 2014;Morgan, 2011;Romito & Beltramini, 2011;Traeen & Daneback, 2013;Sun, Miezan, Lee, & Shim, 2014;Svedin, Åkerman, & Priebe, 2011). Furthermore, Rosenburg and Kraus (2014) reported that 98% of the men they sampled had masturbated while viewing pornography and in Franczyk, Cielecka, and Tuszyńska-Bogucka (2014) 93.1% of the sample self-identified as current pornography users.…”
Section: Overall Prevalencementioning
confidence: 99%
“…The smaller-scale studies identified as part of this review typically reported the percentage of participants who had seen pornography at some point in their lives. Fourteen studies were identified in which more than 90% of the men sampled reported having viewed pornography at some point (Blais-Lecours, Vaillancourt-More, Sabourin, & Godbout, 2016;Bulot, Leurent, & Collier, 2015;D'Abreu, 2013;Donevan & Mattebo, 2017;Drouin & Miller, 2016;Gonsalves, Hodges, & Scalora, 2015;Hald & Mulya, 2013;Kvalem, Traeen, Lewin, & Štulhofer, 2014;Morgan, 2011;Romito & Beltramini, 2011;Traeen & Daneback, 2013;Sun, Miezan, Lee, & Shim, 2014;Svedin, Åkerman, & Priebe, 2011). Furthermore, Rosenburg and Kraus (2014) reported that 98% of the men they sampled had masturbated while viewing pornography and in Franczyk, Cielecka, and Tuszyńska-Bogucka (2014) 93.1% of the sample self-identified as current pornography users.…”
Section: Overall Prevalencementioning
confidence: 99%
“…Tyto výsledky zdůrazňují, že je důležité věnovat pozornost duševnímu zdraví adolescentů, pokud jde o jejich chování na internetu, s ohledem na související rizikové a ochranné faktory, a to vzhledem k jeho úzkému vztahu k sexuální viktimizaci na internetu. Drouin a Miller (2016) zkoumali souvislosti mezi závislostí na internetu, užíváním online erotiky (včetně používání pornografie a internetových chatů zaměřených na sex) a rizikovým online sexuálním chováním (posílání sexuálně explicitních obrázků těm lidem, které známe pouze online -sexting), a off-line sex s těmi, které známe pouze z online prostředí. Výsledky ukázaly, že v dospělé populaci se do většiny online sexuálních aktivit zapojují více muži než ženy.…”
Section: Sexualita V Kyberprostoruunclassified
“…It is difficult to assess the prevalence of and to find accurate statistics on sex addiction on the Internet (8). The reasons are the ever-expanding number of internet users and the difficulty of identifying crimes there because of online erotica usage as a linker between internet addiction and engagement in risky online sexual behaviors (9,10).…”
Section: Introductionmentioning
confidence: 99%